Molecular Identification and Diversity of Pestalotiopsis, Neopestalotiopsis and Pseudopestalotiopsis Species from Four Host Plants in Sarawak, Borneo Island (Malaysia) - Lateef, Adebola; M., Sepiah; M. H., Bolhassan (Journal of Science and Technology, 2018)
Until recently, Pestalotiopsis species have been identified based on host relationship and conidial dimensions. Pestalotiopsis species occur as endophytes, saprobes and also pathogens of many plant hosts. This study used molecular phylogenetic relationships based on ITS sequence data to identify Pestalotiopsis, Neopestalotiopsis and Pseudopestalotiopsis species in addition to their conidial pigmentation from four host plants namely Macaranga triloba, Macaranga sp., Shorea macrophylla and Syzygium sp. Based on the molecular phylogenetic analysis of 18 Pestalotiopsis-like isolates from the four different host plants, the isolates clustered separately into three clades corresponding to their conidial morphology and conidial median cell pigmentation as Neopestalotiopsis, Pestalotiopsis, and Pseudopestalotiopsis irrespective of their host plant association. Among the four host plants studied, S. macrophylla hosts the highest diversity of Pestalotiopsis-like species while Syzygium sp. had the lowest diversity. This is the first report on the molecular phylogenetics and diversity of Pestalotiopsis, Neopestalotiopsis and Pseudopestalotiopsis species from Sarawak, Malaysia in line with recent re-classification in the genus. New records of Pestalotiopsis-like species were also recorded on new host plants.